2021
DOI: 10.1371/journal.pone.0261589
|View full text |Cite
|
Sign up to set email alerts
|

Discretionary Effort on Green Technology Innovation: How Chinese Enterprises Act when Facing Financing Constraints

Abstract: Firm’s effort on Green technology innovation (hereafter, called G-innovation) is affected by financing constraints, and firm will make a discretionary choice according to its own situation, to achieve the maximization of self-interests. Based on the data of Chinese micro enterprises, firstly, we empirically analyze firms’ decision-making towards G-innovation when faced with financing constraints. It supports the view that financing constraints can hinder enterprise technological innovation. And we also make an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Specifically, from an economic perspective, the green collaborative innovation of enterprises and financial institutions mainly involves the interest game of the two parties. In addition, green innovation has a long period for profit realization and a higher social income than personal income [26]. Therefore, the government should conduct environmental supervision to achieve the ideal stable state of game between enterprises and financial institutions.…”
Section: Basis Of the Evolutionary Game Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, from an economic perspective, the green collaborative innovation of enterprises and financial institutions mainly involves the interest game of the two parties. In addition, green innovation has a long period for profit realization and a higher social income than personal income [26]. Therefore, the government should conduct environmental supervision to achieve the ideal stable state of game between enterprises and financial institutions.…”
Section: Basis Of the Evolutionary Game Modelmentioning
confidence: 99%
“…In view of this, the premise of the formulation of ER by the government is to clarify the main participants of collaborative innovation and their interest relationships. Enterprises are the main body of green collaborative innovation [23], but the cycle of green innovation is long, the risk is great, and the social benefit is greater than the personal benefit [25][26], so the green innovation of enterprises often faces high financing constraints [27]. At this time, enterprises will reduce green innovation to maximize their own interests.…”
Section: Introductionmentioning
confidence: 99%
“…Another critical factor to GE practices is technological advancements (C21). While the concept of GE practices has been debated for many years, locating suitable technology to assist with GE practices is still not properly resolved and immature (Zhang et al, 2021). Moreover, if some technology is found to be efficient in ensuring GE practices, it is expensive.…”
Section: Degree Of Prominencementioning
confidence: 99%
“…Wang et al [12] further observed how formal financing constraints hinder the growth of enterprises in China. As for firm innovation, especially in the face of high financing constraints, firms' investment in green technology innovation was greatly reduced in China [19,20].…”
Section: Related Literature and Development Of Hypotheses 221 The Eff...mentioning
confidence: 99%
“…The effects of financing constraints in emerging markets have been widely investigated by scholars [11,12]. Regarding the consequences of financing constraints, several factors are considered such as firm investment [13,14], firm size [15], and firm performance; including firm growth [12,16], firm productivity [8,17,18], and firm innovation [19,20]. The literature has expanded our understanding of diverse impacts of financing constraints on firms in emerging economies.…”
Section: Introductionmentioning
confidence: 99%